UPDATE ON SENTINEL LYMPH NODE MAPPING IN ENDOMETRIAL CANCER PATIENTS WITH A HIGH RISK FOR NODAL METASTASIS - Basaran, Derman (Indian J Gynecol Oncol, 2020)
Surgery is the mainstay of treatment for the majority of patients diagnosed with endometrial carcinoma. Systematic lymphadenectomy has traditionally been considered a standard part of surgical therapy. More recently, however, the value of this has been a subject of much debate. The sentinel lymph node (SLN) mapping algorithm has emerged as an acceptable alternative to conventional pelvic and para-aortic lymph node dissection in endometrial cancer. Clinical trials have demonstrated the accuracy of SLN mapping in detecting nodal spread in patients with endometrial cancer. However, data regarding the oncological outcomes of this approach, particularly in the setting of endometrial cancer with a high risk of nodal spread, is still lacking. In this review, we provide an overview of SLN mapping in endometrial cancer. We will specifically discuss its use in patients with a high risk for nodal metastasis. Controversies and future directions for research will also be discussed.